The BMJ Editorial Scholar 2025/2026 (BMJ, 2025)
Objective To evaluate the effects of intravenous iron on red cell transfusion and recovery after cardiac surgery. Design International, multicentre, double blind, placebo controlled randomised trial (ITACS). Setting 33 hospitals across 10 countries. Participants were enrolled between July 2016 and December 2023. Participants 955 adults with anaemia undergoing elective cardiac surgery. Exclusion criteria included haemoglobinopathy or iron storage disorder, renal dialysis, and erythropoietin or intravenous iron given in the previous four weeks. Intervention A computer generated program randomised participants to intravenous iron 1000 mg or placebo 1-26 weeks before surgery. Participants, clinicians, and data collectors were masked to the intervention. Main outcome measures The number of days alive and at home up to 90 days after surgery (primary outcome), red cell transfusion requirements and complications (secondary outcomes). Results Of 2993 screened participants, 955 were enrolled and 921 of the eligible 939 modified intention-to-treat participants were assessed for the primary outcome. The median number of days alive and at home up to 90 days after surgery was 81.1 (interquartile range 74.8-83.7) in patients assigned to intravenous iron and 80.0 (69.5-83.6) in those receiving placebo (adjusted median difference 1.0 day, 95.4% confidence interval 0.0 to 2.1 days, P=0.041). Red cell transfusions were given to 262 patients (61.1%) in the iron group and 302 (68.2%) in the placebo group during their hospital stay (relative risk 0.90, 95% confidence interval 0.82 to 0.99, P=0.027). No differences were observed for major complications or length of hospital stay. Conclusion Among patients with anaemia undergoing elective cardiac surgery, preoperative intravenous iron was associated with a reduction in red cell transfusion and a small improvement in the number of days alive and at home in the first 90 days after surgery. Intravenous iron is an effective component of patient blood management in this setting. Trial registration ClinicalTrials.gov NCT02632760.